Nutrient requirement for Bush Jasmine (Jasminum sambac Ait.) - Asha Raj (Department of Horticulture, College of Agriculture, 1999)
The investigation "Nutrient requirement of bush jasmine, Jasminum sambac Ait." was conducted at Department of Horticulture, College of Agriculture, Vellayani, Thiruvananthapuram during 1996-'98 inorder to standardise the requirement of major nutrients (N, P and K) for the growth of flowering of bush jasmine. The treatments consisted of factorial combinations of three levels each of nitrogen (50, 100 and 150 kg N ha"), phosphorus (50, 100 and 150 kg P20S ha-I) and potassium (50, 100 and 150 kg ~20 ha") with two controls. The experiment was laid out as 33 + 2 Factorial Randomised Block Design with three replications .. Vegetative characters like the length of main shoot, number of primary and secondary branches, length of primary and secondary branches, North-South and East-West spread of the bush, were significantly higher at the highest level of major nutrients viz., 150 kg N, 150 kg P20S and 150 kg K20 ha'. At the maximum level of major nutrients with 150 kg N : 150 kg P20S : 150 kg K20 ha'", yield of flower buds was found significantly higher. Other flowering characters like monthly yield pattern and weight of hundred flower buds were not found to be influenced by nutritive